2009
DOI: 10.1155/2009/625672
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Differentiation of Deep-Sea Mussels of the GenusBathymodiolus(Mytilidae, Bathymodiolinae)

Abstract: We sequenced the mitochondrial ND4 gene to elucidate the evolutionary processes of Bathymodiolus mussels and mytilid relatives. Mussels of the subfamily Bathymodiolinae from vents and seeps belonged to 3 groups and mytilid relatives from sunken wood and whale carcasses assumed the outgroup positions to bathymodioline mussels. Shallow water mytilid mussels were positioned more distantly relative to the vent/seep mussels, indicating an evolutionary transition from shallow to deep sea via sunken wood and whale ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 42 publications
13
79
0
Order By: Relevance
“…These two subclades formed a single clade supported by high bootstrap values. These results support the previous studies (Kyuno et al, 2009;Lorion et al, 2010;Miyazaki et al, 2010) that proposed the independence of the lineage of B. aduloides and B. manusensis among Bathymodiolus spp., and similarity of the unidentified mussels of Lau Basin and New Zealand to B. manusensis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These two subclades formed a single clade supported by high bootstrap values. These results support the previous studies (Kyuno et al, 2009;Lorion et al, 2010;Miyazaki et al, 2010) that proposed the independence of the lineage of B. aduloides and B. manusensis among Bathymodiolus spp., and similarity of the unidentified mussels of Lau Basin and New Zealand to B. manusensis.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, this is the first report on the new distribution of B. aduloides at the Izu-Ogasawara area, an island arc that extends longitudinally along the edge of the north-eastern Philippine Sea Plate (Figure 4). This distribution pattern is similar to those of two other bathymodiolin mussels, B. japonicus and B. platifrons: these mussels inhabit both vents in Okinawa Trough and cold seep in Sagami Bay, of which the distance is approximately 1500 km (Kyuno et al, 2009). However, as these two species harbour methanotrophic symbionts (Fujiwara et al, 2000), their distribution is limited by availability of methane.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, the previous genetic analysis, based on a partial sequence of the mitochondrial NADH dehydrogenase 4 (ND4) gene, revealed that B. marisindicus shared a haplotype with the congeneric B. brevior in the North Fiji Basin and with B. septemdierum in the Myojin Knoll (Kyuno et al 2009). The sequence of the ND4 gene is widely used in population genetic analyses as it is contains sufficient information to perform such analyses (Kyuno et al 2009), therefore, the results of Kyuno et al (2009) raise the possibility that these three species may be geographic variations of a single species, that has a high dispersal ability.…”
Section: Distribution and Connectivity Of Vent Faunamentioning
confidence: 99%